Effects of Aromatic Thiol Capping Agents on the Structural and Electronic Properties of CdnTen (n = 6,8 and 9) Quantum Dots - Imran, Muhammad; Saif, Muhammad Jawwad; Farooq, Tahir; Iqbal, Javed (Frontiers in Materials, 2021)
Thiols are efficient capping agents used for the synthesis of semiconductor and metal nanoparticles. Commonly, long-chain thiols are used as passivating agents to provide stabilization to nanoparticles. Theoretical methods rarely reported aromatic thiol ligands' effects on small-sized CdTe quantum dots' structural and electronic properties. We have studied and compared the structural and electronic properties of (i) bare and (ii) aromatic thiols (thiophenol, 4-methoxybenzenethiol, 4-mercaptobenzonitrile, and 4-mercaptobenzoic acid) capped CdnTen quantum dots (QDs). Aromatic thiols are used as thiol-radical because of the higher tendency of thiol-radicals to bind with Cd atoms. This work provides an understanding of how the capping agents affect specific properties. The results show that all aromatic thiol-radical ligands caused significant structural distortion in the geometries. The aromatic thiol-radical ligands stabilize LUMOs, stabilize or destabilize HOMOs, and decrease HOMO-LUMO gaps for all the capped QDs. The stabilization of LUMOs is more pronounced than the destabilization of HOMOs. We also studied the effect of solvent on structural and electronic properties. TD-DFT calculations were performed to calculate the absorption spectra of bare and capped QDs, and all the capping ligands resulted in the redshift of absorption spectra.